Захист навколишнього середовища від шкідливих викидів оксидів азоту при роботі котлів - Єфімов, Олександр В'ячеславович; Тютюник, Лариса Іванівна; Касілов, Віктор Йосипович; Іванова, Лідія Анатоліївна (НТУ "ХПІ", 2018)
Стаття присвячена розвитку методів захисту навколишнього середовища від шкідливих викидів оксидів азоту при роботі парових та водогрійних котлів. Скорочення викидів оксидів азоту в атмосферу димовими газами принципово може бути здійснено по таких основних напрямах: застосування спеціальних технології спалювання палива, що запобігає значному окисленню азоту, зокрема використання для горіння в якості окислювача кисню; застосування рідких або твердих сорбентів, що поглинають з димових газів оксиди азоту з подальшою регенерацією і отриманням товарних форм зв’язаного азоту; каталітичне розкладання оксиду азоту на елементарний азот і кисень.

This scientific paper is devoted to the development of the methods of environmental protection from unhealthy nitrogen oxides emitted by operating steam and hot-water boilers. Emission of nitrogen oxides into the atmosphere with flue gases can be reduced by using special fuel combustion technologies that considerably decrease the nitrogen oxidation, for example oxygen can be used as an oxidizer during the combustion process or liquid and solid sorbents that absorb nitrogen oxides from flue gases can be used with the subsequent regeneration that results in the production of commercial bound nitrogen. A technology of catalytic decomposition of nitrogen oxide into elementary nitrogen and oxygen can also be used. The main sources of anthropogenic environmental pollution are the fuel and energy sector, power engineering, transport and industry that deal with combustion processes. First of all these are low-temperature heat, carbon dioxides, nitrogen oxides, dust, slag, sulfur oxides, and ash. Pollution of the atmosphere, earth and water with harmful emissions aggravates sanitary and hygiene state of the cities, towns, water ponds, fields, woods, the human body and the vegetation. It degrades the quality of produced products, speeds-up the wear of mechanisms and results in the destruction of building structures, houses and facilities.
Protecting environment from unhealthy nitrogen oxide emissions of operating boilers
Keywords: котел паровий; котел водогрійний; паливо органічне; оксид азоту; домішки шкідливі; сірка; пил; шлак; оксид сірки; зола; steam boiler; hot-water boiler; organic fuel; nitrogen oxides; harmful admixtures; environment